TuMV triggers stomatal closure but reduces drought tolerance in Arabidopsis - Manacorda, Carlos Augusto (2021)
Compatible plant viral infections are a common cause of agricultural losses worldwide. Characterization of the physiological responses controlling plant water management under combined stresses is of great interest in the current climate change scenario. We studied the outcome of TuMV infection on stomatal closure and water balance, hormonal balance and drought tolerance in Arabidopsis. TuMV infection reduced stomatal aperture concomitantly with diminished gas exchange rate, daily water consumption and rosette initial dehydration rate. Infected plants overaccumulated salicylic acid and abscisic acid and showed altered expression levels of key ABA homeostasis genes including biosynthesis and catabolism. Also the expression of ABA signalling gene ABI2 was induced and ABCG40 (which imports ABA into guard cells) was highly induced upon infection. Hypermorfic abi2-1 mutant plants, but no other ABA or SA biosynthetic, signalling or degradation mutants tested abolished both stomatal closure and low stomatal conductance phenotypes caused by TuMV. Notwithstanding lower relative water loss during infection, plants simultaneously subjected to drought and viral stresses showed higher mortality rates than mock-inoculated drought stressed controls, alongside downregulation of drought-responsive gene RD29A. Our findings indicate that despite stomatal closure triggered by TuMV, additional phenomena diminish drought tolerance upon infection.